Membranous nephropathy in Turkey: Turkish society of nephrology glomeruler diseases (TSN-Gold) database results - Yıldız, Abdülmecit; Ulu, Memnune Sena; Oruç, Ayşegül; Uçar, Ali Rıza; Öztürk, Savaş; Alagöz, Selma; Eren, Necmi; Koçyiğit, İsmail; Köksal Cevher, Şimal; Haras, Ali Burak; Şumnu, Abdullah; Arınsoy, Turgay; et al. (Oxford University Press, 2020)
[Abstract Not Available]
Keywords: TSN-Gold; Membranous Nephropathy; Glomeruler Diseases